PERLUNYA PEMBINAAN TERHADAP DEWASA AWAL DALAM MENGHADAPI TUGAS PERKEMBANGANYA - Eka Yolanda Siregar; Ester Magdalena Nababan; Eunike Rehulina Ginting; Benita A Nainggolan; Dian Lorensa Ritonga; Damayanti Nababan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
Early adulthood is a period of livelihood, discovery, consolidation and reproductive period, which is a period full of problems and emotional tension, a period of social isolation, a period of commitment and dependence, changes in values, creativity and adjustment to a new lifestyle. During this transition period he will enter his Developmental Task. On the other hand, he will be faced with a problem, including problems within himself (personal hazard), his physique (Physical hazard), and problems with society (social hazard). The method used in this paper is a qualitative method with a library approach. A literature study was conducted by reviewing various sources related to the topics discussed as a conclusion that early adulthood is a period that is not easy, many developmental tasks will be faced, problems that come and go so that many early adults do not know the direction of their life, therefore it is necessary to have a coaching to direct and guide early adults so that they become strong and strong adults in facing the tasks they will carry.